2009
DOI: 10.1080/14017430902785501
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cardiac 64-slice computed tomography: Importance of coronary calcium

Abstract: The diagnostic accuracy of CTA in patients with no or little coronary calcium is excellent. However, in patients with an Agatston score >400 specificity declines and therefore, these patients should not go on to CTA, but be referred to CA instead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Of the 19 eligible studies, 15 studies [6-11, 13, 14, 20-26] provided per-segment data, five studies provided per-artery data [6,9,11,25,27] and 11 studies provided per-patient data [6,10,11,13,16,24,[27][28][29]. Four studies used dual-source 64-slice CTA [9,11,13,26].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Of the 19 eligible studies, 15 studies [6-11, 13, 14, 20-26] provided per-segment data, five studies provided per-artery data [6,9,11,25,27] and 11 studies provided per-patient data [6,10,11,13,16,24,[27][28][29]. Four studies used dual-source 64-slice CTA [9,11,13,26].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Theoretically, such studies could evaluate the use of NECT as a screening tool by using a lower radiation dose optimised to the energy of calcium for the purpose of measuring calcium volume; this could theoretically be a quick screening tool or even used in conjunction with duplex imaging. Also, similar to what has been described in recent cardiology literature, the carotid calcium volume could be utilised as part of a scoring system or as an adjunct with additive diagnostic value to the CTA [39,40]. This study also raises the possibility that, in theory, a relatively simple, semiautomated technique could be developed whereby computer software could help measure calcified plaque that is not obscured by intravascular contrast.…”
Section: Discussionmentioning
confidence: 86%
“…Another potential limitation is that helical CT is well known to be sensitive (88%) but not very specific (52%) in detecting a .50% coronary stenosis [38]. Nonetheless, recent articles in the cardiology literature strongly suggest that there is additive diagnostic value of the coronary calcium score to the coronary angiogram, presumably owing to the limitation of percent stenosis in reflecting the severity of the atherosclerotic disease process, especially during the early stages of the vessel wall changes and positive remodelling [39,40]. Hence, it has yet to be prospectively studied as to whether carotid calcium volume or other scoring methods will have similar measurement variability between observers and if the specificity will be higher than that of coronary calcium.…”
Section: Discussionmentioning
confidence: 99%
“…However, arterial wall calci cation may adulterate the results of CTA, reducing the speci city and positive predictive value. Diederichsen et al 29 reported that the diagnostic accuracy of CTA declined in patients with high CAC Agatston score 400 and suggested that patients with CS 400 should not undergo CTA. On the other hand, Lau et al 30 found that a high CAC improved the sensitivity of CTA in detecting a stenotic coronary artery, without compromising speci city.…”
Section: Discussionmentioning
confidence: 99%